ARAP1 is an independent prognostic biomarker in older women with ovarian high-grade serous adenocarcinoma receiving first-line platinum-based antineoplastic therapy. (2nd January 2020) - Nadaraja, Sambavy; Schledermann, Doris; Herrstedt, Jørn; Østrup, Olga; Ditzel, Henrik J.; ,
Abstract: Background: Little is known about the biological factors influencing ovarian cancer (OC) patient outcome, especially in older patients who are often underrepresented in clinical trials. We examined alterations in the transcriptomic profile of primary high-grade serous carcinoma (HGSC) samples from older OC patients (>70 years) receiving first-line platinum-based treatment to identify potential biomarkers for prediction of response to this therapy. Material and methods: Tumor samples from 50 HGSC patients were identified from a retrospective cohort, analyzed by gene expression array. The protein expression of selected biomarkers was examined using immunohistochemistry (IHC). Results: Gene expression profiling revealed 81 genes with significantly altered expression in patients experiencing progression after first-line platinum-based treatment within 6 months versus those who progressed later than 12 months. Expression of ankyrin repeat and PH domain 1 (ARAP1) was significantly lower in the group with early versus late progression ( p ≤ .01). Correlation between ARAP1 expression and outcome was further confirmed by IHC staining in the discovery cohort ( χ 2 -test, p = .004) and in independent validation cohorts. The sensitivity of ARAP1 allowed identification of 64.7% of patients with early progression in the discovery population, with a specificity of 78.6% and a negative predictive value of 78.6%. Multivariate regression analysis identified ARAP1 as an independent prognostic factor. Conclusions: This hypothesis generating study suggests that low expression of ARAP1 is an independent prognostic biomarker of shorter RFS in older patients with HGSC receiving first-line platinum-based antineoplastic therapy, which could be used to identify patients who should receive more intensive treatment and closer surveillance.